Pile optimization in slope stabilization by 2D and 3D numerical analyses. Issue 2 (7th February 2022) - Benmebarek, Mohamed Amine; Benmebarek, Sadok; Rad, Majid Movahedi; Ray, Richard
ABSTRACT: In this paper, numerical computations using PLAXIS 2D and 3D have been conducted to optimize a row of piles in cohesive-frictional slope stabilization. First, 2D parametric studies were performed to identify both the optimal location and length of the pile as well as the effect of pile head conditions. Next, more rigorous parametric studies taking account of the exact geometry was carried out using 3D analyses. According to the obtained results, the fixed pile head located at the slope middle better improves the stability and reduces the optimal length of the pile. Piles with free head contribute marginally to the increased factor of safety of cohesive-frictional slope. In 3D analyses, it is shown that spacing ratio beyond S/D = 4 ( S : pile spacing, D : diameter of the pile), the soil will flow between piles leading to a total vanish of the arching effect when S/D exceeds 12. Comparing the results, the limitation of 2D analysis for piled cohesive-frictional slope is highlighted.